Effect of selective and non-selective beta blockade on pulmonary function and tracheobronchial mucociliary clearance in healthy subjects. - Pavia, D (1986)
A controlled, double blind, crossover study was carried out to ascertain the effect of single doses of selective (100 mg atenolol) and non-selective (160 mg propranolol) beta blocker on pulmonary function and tracheobronchial mucociliary clearance. The study group comprised 12 healthy, young subjects. Adequate and comparable blockade was achieved with both drugs, the administration of which resulted in significantly lower pulse rates (at least up to eight hours after administration of the drug) and systolic blood pressures (three hours after drug administration) than were found with placebo. Small (of the order of 5%) but nevertheless statistically significant falls in FEV1 and forced vital capacity accompanied the administration of both beta blockers (but not the placebo) and were measurable up to eight hours after administration of the drug. Indices of pulmonary function had returned to normal by the next day. Peak expiratory flow and indices of small airways function remained unaltered after beta blockade. Mean tracheobronchial mucociliary clearance was depressed after administration of both beta blocking drugs, although the reduction was significant (p less than 0.05) only when propranolol was compared with placebo.